Regulation mechanism of Rosa roxburghii Tratt. (Cili) fruit vinegar on non-alcoholic fatty liver disease - Wang, Yu; Lang, Rui; Li, Lilang; Wen, Yonglan; Gao, Ming; Zhang, Jie; Yang, Juan; Li, Qiji; Wang, Li; Yang, Xiaosheng; Wang, Xiaolong; Xie, Chunzhi (Frontiers in Nutrition, 2025)
BackgroundNon-alcoholic fatty liver disease (NAFLD) is a chronic liver disease characterized by the excessive accumulation of lipids as a pathological feature. Previous studies have demonstrated that Rosa roxburghii Tratt. fruit vinegar (RFV) played an important role in intervening in obesity and related complications by regulating the intestinal microbiota in high-fat diet mice.MethodsThis study investigated the mechanisms by which RFV improves NAFLD from multiple perspectives. Potential targets were predicted by network pharmacology and molecular docking analyses. Intestinal microbial communities were detected and analyzed using 16S rRNA gene sequencing technology. Liver metabolites were detected and analyzed using ultra high performance liquid chromatography quadrupole-exactive high field-X mass spectrometer (UHPLC-Q-Exactive HF-X) and Progenesis QI software. Hepatic protein expression levels were detected and quantified using Western blotting analysis and gray-value analysis, respectively.ResultsThe results indicated that, RFV could improve the diversity of intestinal microbiota in NAFLD mice, reduce the ratio of Firmicutes to Bacteroidetes (F/B), and reverse the relative abundance of differential bacteria genera related to lipid accumulation and energy metabolism. The intestinal microbiota was correlated with the levels of lipid metabolism and oxidative stress in the serum and liver of mice with NAFLD. The primary bacteria genera involved were Allobaculum, Faecalibaculum, Dubosiella, Blautia, and unclassified_f_Lachnospiraceae. A total of 441 liver metabolites were identified in NAFLD mice and participating in 21 metabolic pathways. Glycerophospholipid metabolism may be an important pathway regulating NAFLD by RFV. Phosphatidylcholines (PC) and lysophosphatidylcholinergic (LPC) metabolites were significantly regulated by RFV and had significant correlation with differential microbiota. RFV may improve NAFLD by regulating lipid synthesis in the adenosine 5’-monophosphate (AMP)-activated protein kinase (AMPK) pathway. Western blotting analysis showed that, RFV could activate the AMPK phosphorylation, and reduce the expression of fatty acid synthase (FASN) and sterol regulatory element-binding protein 1 (SREBP-1c), resulting in the inhibition of fatty acids de novo synthesis and lipid accumulation.ConclusionAs a functional food, RFV has been proven to be effective in improving NAFLD. The underlying mechanisms involve the modulation of the intestinal microbiota and metabolites balance, and regulation on lipid disorders through AMPK signaling pathway.